2011
DOI: 10.1051/0004-6361/201016302
|View full text |Cite
|
Sign up to set email alerts
|

Chemical spots in the absence of magnetic field in the binary HgMn star 66 Eridani

Abstract: Context. According to our current understanding, a subclass of the upper main-sequence chemically peculiar stars, called mercurymanganese (HgMn), is non-magnetic. Nevertheless, chemical inhomogeneities were recently discovered on their surfaces. At the same time, no global magnetic fields stronger than 1-100 G are detected by systematic studies. Aims. The goals of our study are to search for a magnetic field in the HgMn binary system 66 Eri and to investigate chemical spots on the stellar surfaces of both comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 40 publications
(78 reference statements)
4
43
1
Order By: Relevance
“…Numerous investigations of magnetism in such stars (e.g. Borra & Landstreet 1980;Glagolevskij et al 1985;Shorlin et al 2002;Aurière et al 2010;Makaganiuk et al 2011) have found no convincing evidence for fields in this class of stars with uncertainties often in the range of a few G up to a few tens of G. Furthermore, α And has been specifically investigated with the MuSiCoS (13 observations, typical σ ∼ 30-60 G) and ESPaDOnS (5 observations, typical σ ∼ 6-19 G) spectropolarimeters without any significant detection of a nonzero longitudinal field or of any Stokes V signature indicative of a non-zero field ).…”
Section: Repeated Observations Of Non-magnetic Starsmentioning
confidence: 99%
“…Numerous investigations of magnetism in such stars (e.g. Borra & Landstreet 1980;Glagolevskij et al 1985;Shorlin et al 2002;Aurière et al 2010;Makaganiuk et al 2011) have found no convincing evidence for fields in this class of stars with uncertainties often in the range of a few G up to a few tens of G. Furthermore, α And has been specifically investigated with the MuSiCoS (13 observations, typical σ ∼ 30-60 G) and ESPaDOnS (5 observations, typical σ ∼ 6-19 G) spectropolarimeters without any significant detection of a nonzero longitudinal field or of any Stokes V signature indicative of a non-zero field ).…”
Section: Repeated Observations Of Non-magnetic Starsmentioning
confidence: 99%
“…For the second software package we used the LSD technique (Donati et al 1997;Kochukhov et al 2010). The details of the analysis procedure can be found in Makaganiuk et al (2011) and Fossati et al (2013). About 170 lines were used in the line mask, but a test with the 80 lines used for the SVD program package did not show any significant difference in the results.…”
Section: Magnetic Field Measurements Using Harpsmentioning
confidence: 99%
“…The Hg ii λ3984 line is variable in most HgMn stars, but there are exceptions (66 Eri A; Makaganiuk et al 2011b). Conversely, there are cases where the variations are dramatic for the Hg lines, but are (if any) below the detection limit for lines of other elements (α And; Wade et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…To allow for a more robust normalisation of Hg ii λ3984, the red wing of H was used to define pseudocontinuum regions. (Hubrig et al 2006(Hubrig et al , 2011Savanov et al 2009), 66 Eri A (Makaganiuk et al 2011b), α And A (Adelman et al 2002;Kochukhov et al 2007), and φ Phe (Makaganiuk et al 2012;Korhonen et al 2013). All the stars discussed here are slow or moderately fast rotators with equatorial velocities below 55 km s −1 and rotation periods in the range 2-10 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation